Monitoring and control of material surface evenness in the Dosimat Feeder Hopper at Finish Mill V PT Semen Padang - Nafisa, Rahmi; Mirshad, Emilham (Journal of Industrial Automation and Electrical Engineering, 2025)
The dosimat feeder is a device used to weigh additional materials before entering the mill for grinding. It includes a hopper that functions as temporary storage before the material is transferred to the belt conveyor. The main issues addressed in this study are frequent material shortages that can disrupt industrial operations, and uneven filling that may affect system performance and reduce production efficiency. This research adopts the Research and Development (R&D) method, aiming to develop a product and evaluate its effectiveness. The system is designed using an Arduino Uno microcontroller to process data from sensors. Ultrasonic sensor 1 is configured to control material filling, while ultrasonic sensors 2, 3, and 4 are used to monitor material evenness, with a maximum distance tolerance of 2 cm for ultrasonic sensor 1. A DC vibrator motor is activated when the material inside the hopper is detected to be uneven. The results of the study show that the material level and surface flatness status are successfully displayed on a 16x2 LCD.